Advancing female education by improving democratic institutions and women's political representation - Francesco Burchi; Luis A. Camacho (Deutsches Institut für Entwicklungspolitik (DIE), 2014)
Reducing gender gaps in education, employment and political decision making, among other dimensions, has long been an important development objective. This is confirmed by the international consensus reached over Millennium Development Goal 3 (MDG 3): “Promote Gender Equality and Empower Women”. Ensuring equal access to education, in particular, is a central component of this effort, as reflected in the goal's target, which is to eliminate gender disparities in education by 2015. Are countries that have adopted democratic political institutions more successful at reducing the gender gap in education? And can higher levels of political representation of women contribute to achieving this objective? Democracy advances the cause of women's education in the absolute, although there is no conclusive evidence on whether it improves women's situation relative to men's. When it comes to political representation, the evidence is clear: larger numbers of women in politics and elected office improve overall educational outcomes and reduce the gender gap in education. What lessons can be learnt regarding the linkages between democratic institutions, women's political representation and the gender gap in education? - The fact that democracies have a better track record than autocratic regimes when it comes to education and development provides additional justification for development cooperation policies that support gradual political opening in autocracies as well as the stabilisation and consolidation of democracy in countries that have chosen to go down this path. Moreover, it suggests that the adoption of specific democratic institutions, such as allowing women to run for office, can make a difference, even in countries that are not formally democratic. - Multiple policy objectives could be reached with one policy tool: women's political representation. Progress in this dimension improves not only girls' education but also health and political participation, among other outcomes. - Policy-makers and international donors should exercise caution in adopting and supporting the implementation of quick fixes to increase women's political representation, such as gender quotas. In countries with high levels of gender inequality, such as India, quotas alone are likely to have limited effects. Instead, these should be integrated into a larger set of interventions aimed at diminishing gender gaps in employment, assets and decision making. Overall, these arguments speak directly to the current debate on the post-2015 agenda. The ratio of girls to boys in education and the proportion of seats held by women in national parliament are two indicators for MDG 3. As these topics are also likely to be central in the post-2015 agenda, it is important to consider the studies showing that making progress in the second indicator advances the first one. This, in fact, can help when analysing the feasibility of these objectives and in the planning of the resources required to achieve them. Moreover, these findings point to the importance of including governance in the global develop¬ment agenda.
Keywords: 330; Gender; Governance